JEJARING KEKUASAAN AKTOR DALAM PENGELOLAAN HUTAN MANGROVE BERBASIS MASYARAKAT DI PROVINSI ACEH - Oka Hasnanda (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2019)
The research of actors' power network in community-based mangrove management aims to analyze the interaction and dynamics of actors in forest management networks by local communities through a power approach. Networks can be seen as the arena and interaction of actors in the distribution of information exchange, policy and coordination, allowing only influential actors to influence weak actors in the network. Investigation of the role of these actors through the network establishes the interactional relationships between individuals, groups, or organizations that influence behavior. Through the network it can be judged that every actor (individual or group) has different access to resources (wealth, power, or information). The actor's analytical approach refers to the framework of centralized power actors (ACP), which is an analytical approach for understanding the empirical resources of actors in socio-political relationships and contributing to strongly empirically identified groups of powerful actors. Thus ACP can serve as a tool for the assessment of power networks, useful as preliminary information in forest policy practice. While to know the relationship between network with social network analysis approach (SNA).